Seminar On Improving Entrepreneurship Spirits Of Export Business (Marketing Aspects) - Agnes Oktavia Gultom; M. Alkadri Perdana (CiDEA Journal, 2024)
Abstract This seminar aims to support the development of the abilities of students and the general public in understanding more deeply the concept of entrepre-neurship in the export business, as well as providing clear insight into strategies and best practices in the Export Business. Organizing seminars was chosen as a method because it was considered more effective in delivering and receiving ma-terial. The main objective of this final project is to organize a Seminar on increas-ing the entrepreneurial spirit in the export business. The steps taken include searching for and determining sponsor criteria, determining promotional tools such as brochures, advertisements and banners, planning and realizing the promotion-al budget, as well as identifying obstacles that may arise during implementation. This process includes finding solutions to overcome obstacles that arise, and final-ly, evaluating seminar activities through feedback from participants. There were 132 seminar participants, the project results show that the technical aspects of job promotion can be divided into several stages, including searching for project sponsors, determining promotion tools, determining promotion budgets, identifying obstacles, finding solutions to overcome obstacles, and launching the project through participant feedback.